2020
DOI: 10.1186/s13104-020-05356-z
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: why do people keep hurting their back?

Abstract: Objective Low back pain (LBP) is one of the most disabling and costly conditions worldwide. It remains unclear why many individuals experience persistent and recurrent symptoms after an acute episode whereas others do not. A longitudinal cohort study was established to address this problem. We aimed to; (1) evaluate whether promising and potentially modifiable biological, psychological, social and behavioural factors, along with their possible interactions, predict LBP outcome after an acute episode; (2) compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…As sex is an important factor in the modulation of pain, and sex differences in pain behaviors have been reported in other disc puncture studies ( 21 , 116 ), sex differences should be considered in future animal studies. This limitation is somewhat mitigated by findings that women bear the burden of chronic LBP ( 1 , 2 ), sex has been found to inconsistently predict outcomes over 12 months in a human study ( 117 ), and no sex differences in disc height and histopathology changes have been reported ( 21 ). Our design also makes our findings directly relatable to those of Lillyman et al ( 17 ) who studied the effects of disc injury in female rats across 18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As sex is an important factor in the modulation of pain, and sex differences in pain behaviors have been reported in other disc puncture studies ( 21 , 116 ), sex differences should be considered in future animal studies. This limitation is somewhat mitigated by findings that women bear the burden of chronic LBP ( 1 , 2 ), sex has been found to inconsistently predict outcomes over 12 months in a human study ( 117 ), and no sex differences in disc height and histopathology changes have been reported ( 21 ). Our design also makes our findings directly relatable to those of Lillyman et al ( 17 ) who studied the effects of disc injury in female rats across 18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This study analysed data from a data‐intensive cohort study that included extensive collection of biological, behavioural, psychological and social data from individuals who were recruited within 2 weeks of onset of an acute episode of LBP and followed for 12 months (Klyne et al, 2020 ). This analysis involved data from the entire cohort of 133 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited and assessed within 2 weeks of onset of an acute episode of LBP that was preceded by at least 1 month without pain. To ensure participants had experienced an acute LBP episode of sufficient duration and intensity, we employed a two‐phase screening process with respect to pain and disability (Klyne et al, 2020 ). Initially, participants were screened by an automated online screening questionnaire that included participants if their LBP (1) occurred within the last 2 weeks and lasted for at least 24 hours, (2) caused functional limitation and (3) caused them to seek/seriously consider health intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, positive relationships between pain-related fear, LBP intensity and disability have been found in systematic reviews and meta-analyses ( 39 , 42 ), and fear avoidance beliefs have been shown to be associated with poor treatment outcome in patients suffering from LBP within a time period of <6 months ( 43 ). However, the predictive value of pain-related fear regarding the development of LBP is limited ( 39 ) and psychological factors in general (when considered in isolation) explain only a small proportion in outcomes such as pain intensity ( 44 , 45 ). Yet, recent research has shown an association between pain-related fear and dysfunctional motor behavior in LBP patients and healthy individuals ( 46 48 ), indicating significant interactions between psychological factors and motor control (psychomotor interactions), which can promote potential clinically relevant consequences such as limited motor variability, increased paraspinal muscle co-contraction and loading on spinal tissues ( 15 ).…”
Section: Psychological Factorsmentioning
confidence: 99%